Fatal Attraction: Light Pollution Creates an Ecological Trap for Wild Fish - Jules Schligler; Tommy Norin; Megan McBride; Fabien Morat; Shaun S. Killen; Stephen E. Swearer; Ricardo Beldade; Suzanne C. Mills (Global Change Biology, 2026)
Ecological traps, poor‐quality habitats that attract animals, significantly threaten ecosystems but have rarely been documented in marine environments. In fish, early life‐history events, such as larval settlement, play a key role in shaping individual survival, population stability, and community interactions. While evidence suggests that late‐stage fish and invertebrate larvae exhibit a phototactic response, the effects of light pollution on larval settlement and survival remain poorly understood. Here, we simulated environmental light pollution on coral reefs using artificial light to examine its impact on fish settlement and post‐settlement consequences. We found that settlement was up to eight times higher onto corals exposed to light pollution compared to those under natural conditions. However, exposure to light pollution reduced recruit survival by half, desynchronized settlement from the full moon and reduced size at settlement. We identified key mechanisms contributing to increased mortality of individuals exposed to artificial light, including disruptions in resting metabolic rhythm and higher predation (due to heightened predator attraction). Additionally, we reveal potential trait compensation in body condition and maximum metabolic rate, traits linked to fitness. However, despite these potential compensatory mechanisms, light pollution functions as a severe ecological trap for fish, attracting individuals into suboptimal environments where they experience higher mortality. This underscores the need to regulate light pollution as a critical environmental stressor.